Efectividad agronómica y económica de la fertilización líquida en maíz amarillo duro bajo condiciones de secano, en Tosagua - Manabí - Salavarría Alvarado, María Elisia (2022)
The objective of the research was to evaluate the agronomic and economic effectiveness of liquid fertilization in hard yellow maize under rainfed conditions, the MonteDark site, Tosagua. Two corn hybrids INIAP H – 601 and INIAP H – 603 and three fertilization techniques (liquid in superficial drench, liquid in injected drench and granulated fertilization) were tested. In addition, a plot with nitrogen omission was established in order to calculate the agronomic nitrogen efficiency (EAN). The variables recorded were number of commercial ears, EAN (kg of ear kg-1 of N applied) and net economic benefit – BEN (USD ha-1). The data was processed through analysis of variance and separation of means with Tukey α<0.05. The results indicated significant statistical differences (p<0.05) for all the variables evaluated. The highest grain yield was 8,363 for injected liquid fertilization, 7,636 for drench liquid fertilization, and 6,867 kg ha-1 for conventional granular fertilization. The EAN was 25.68 - 21.64 and 17.37 kg of ears kg-1 of N applied, with injected liquid fertilization, in drench and granulated, respectively. The liquid fertilizations in drench and injected reached the highest BEN of the fertilization, with an increase of 422 and 269 USD ha-1, with respect to the granulated fertilization. It is concluded that under rainfed conditions in maize areas in Tosagua, it is more profitable to carry out injected liquid fertilization and superficial drench.